(untitled) (African Disability Rights Yearbook, 2025)
Climate change significantly threatens the health and lives of people with albinism, affecting both their physical and mental well-being. Elevated ultraviolet radiation increases visual impairments and susceptibility to skin cancer, while climate-related disasters further limit access to healthcare. Despite these multifaceted challenges, states in their capacity as duty-bearers are obligated under human rights and climate change frameworks to not only uphold their climate change mitigation and adaptation duties but also their duty to respect, protect, promote, and fulfil the individual’s rights. These obligations as the article submits are related – with the climate change obligations influencing the human rights ones. Heeding the clarion call that ‘no one is left behind’, South Africa has established legal mechanisms to mitigate the impacts of climate change on the rights of persons with albinism, ensuring that they adapt to climate change by undertaking practical measures, such as the provision of protection packages. However, the state’s efforts fall short of achieving full disability inclusivity for persons with albinism in climate related decision-making processes, leading to their marginalisation.